The BRICS' impacts on local economic development in the Global South: the cases of a tourism town and two mining provinces in Zambia - Kragelund, Peter; Carmody, Pádraig (Area development and policy, 2016)
Research on how emerging economies affect other areas of the Global South has flourished in the past decade, and it is now well established that this impact occurs through a variety of channels, but knowledge of local developmental effects is scant. This article seeks to open up this black box by scrutinizing the effects of investments by the BRICS in a tourism town and two mining areas in Zambia. Recently, investments by the BRICS have been heralded as a key driver of structural transformation in the rest of the Global South; however, the lack of linkages and spillovers from BRICS actors to the local economy, in the Zambian case at least, leads instead to continued technological and economic dependence and consequent economic narrowing.